Reduced Triglyceride Secretion in Response to an Acute Dietary Fat Challenge in Obese Compared to Lean Mice - Uchida, Aki; Whitsitt, Mary C.; Eustaquio, Trisha; Slipchenko, Mikhail N.; Leary, James F.; Cheng, Ji-Xin; Buhman, Kimberly K. (Frontiers in Physiology, 2012)
Obesity results in abnormally high levels of triglyceride (TG) storage in tissues such as liver, heart, and muscle, which disrupts their normal functions. Recently, we found that lean mice challenged with high levels of dietary fat store TGs in cytoplasmic lipid droplets in the absorptive cells of the intestine, enterocytes, and that this storage increases and then decreases over time after an acute dietary fat challenge. The goal of this study was to investigate the effects of obesity on intestinal TG metabolism. More specifically we asked whether TG storage in and secretion from the intestine are altered in obesity. We investigated these questions in diet-induced obese (DIO) and leptin-deficient (ob/ob) mice. We found greater levels of TG storage in the intestine of DIO mice compared to lean mice in the fed state, but similar levels of TG storage after a 6-h fast. In addition, we found similar TG storage in the intestine of lean and DIO mice at multiple time points after an acute dietary fat challenge. Surprisingly, we found remarkably lower TG secretion from both DIO and ob/ob mice compared to lean controls in response to an acute dietary fat challenge. Furthermore, we found altered mRNA levels for genes involved in regulation of intestinal TG metabolism in lean and DIO mice at 6 h fasting and in response to an acute dietary fat challenge. More specifically, we found that many of the genes related to TG synthesis, chylomicron synthesis, TG storage, and lipolysis were induced in response to an acute dietary fat challenge in lean mice, but this induction was not observed in DIO mice. In fact, we found a significant decrease in intestinal mRNA levels of genes related to lipolysis and fatty acid oxidation in DIO mice in response to an acute dietary fat challenge. Our findings demonstrate altered TG handling by the small intestine of obese compared to lean mice.